2021
DOI: 10.1002/cncr.33906
|View full text |Cite
|
Sign up to set email alerts
|

A Coala‐T‐Cannabis Survey Study of breast cancer patients' use of cannabis before, during, and after treatment

Abstract: BACKGROUND:The goal of this study was to characterize cannabis use among patients with breast cancer, including their reasons for and timing of use, their sources of cannabis information and products, their satisfaction with the information found, their perceptions of its safety, and their dialogue about cannabis with their physicians. METHODS: United States-based members of the Breastcancer.org and Healthline.com communities with a self-reported diagnosis of breast cancer within 5 years (age ≥ 18 years) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 53 publications
7
44
0
2
Order By: Relevance
“…The online survey of breast cancer sufferers in the US mentioned previously found that the majority of patients (61%) did not discuss cannabis use with their doctor. This survey also revealed that the internet and family/friends were the most common sources of information about cannabis [ 2 ].…”
Section: Potential Barriers To Use In Oncologymentioning
confidence: 99%
See 2 more Smart Citations
“…The online survey of breast cancer sufferers in the US mentioned previously found that the majority of patients (61%) did not discuss cannabis use with their doctor. This survey also revealed that the internet and family/friends were the most common sources of information about cannabis [ 2 ].…”
Section: Potential Barriers To Use In Oncologymentioning
confidence: 99%
“…Of those using cannabis, 79% had used it during treatment (systemic therapies, radiation, surgery) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their letter to the editor, Brasky et al highlight potential selection bias as an important limitation to online convenience sampling. As we acknowledge in our article, 1 online survey study designs do carry inherent limitations. However, they carry key advantages as well and present a valid opportunity to contribute meaningful, complementary patient‐reported data to the literature on medical cannabis use among patients with breast cancer, as our study has.…”
mentioning
confidence: 99%
“…[13][14][15] There remains a significant need for high-quality research examining the use of cannabis-based products beyond "current" or "ever" use in patients with cancer. Almost no study, including this one, 1 has comprehensively examined the use of such products by assessing the frequency, intensity, duration, and dose in people with cancer. Nor have prior studies satisfactorily examined the full complement of cannabis-based products available in a swiftly growing market.…”
mentioning
confidence: 99%